Hodgkin-Reed-Sternberg cells in classical Hodgkin lymphoma show alterations of genes encoding the NADPH oxidase complex and impaired reactive oxygen species synthesis capacity. - Maciej Giefing (Public Library of Science (PLoS), 2013)
The membrane bound NADPH oxidase involved in the synthesis of reactive oxygen species (ROS) is a multi-protein enzyme encoded by CYBA, CYBB, NCF1, NCF2 and NCF4 genes. Growing evidence suggests a role of ROS in the modulation of signaling pathways of non-phagocytic cells, including differentiation and proliferation of B-cell progenitors. Transcriptional downregulation of the CYBB gene has been previously reported in cell lines of the B-cell derived classical Hodgkin lymphoma (cHL). Thus, we explored functional consequences of CYBB downregulation on the NADPH complex. Using flow cytometry to detect and quantify superoxide anion synthesis in cHL cell lines we identified recurrent loss of superoxide anion production in all stimulated cHL cell lines in contrast to stimulated non-Hodgkin lymphoma cell lines. As CYBB loss proved to exert a deleterious effect on the NADPH oxidase complex in cHL cell lines, we analyzed the CYBB locus in Hodgkin and Reed-Sternberg (HRS) cells of primary cHL biopsies by in situ hybridisation and identified recurrent deletions of the gene in 8/18 cases. Immunohistochemical analysis to 14 of these cases revealed a complete lack of detectable CYBB protein expression in all HRS cells in all cases studied. Moreover, by microarray profiling of cHL cell lines we identified additional alterations of NADPH oxidase genes including CYBA copy number loss in 3/7 cell lines and a significant downregulation of the NCF1 transcription (p=0.006) compared to normal B-cell subsets. Besides, NCF1 protein was significantly downregulated (p<0.005) in cHL compared to other lymphoma cell lines. Together this findings show recurrent alterations of the NADPH oxidase encoding genes that result in functional inactivation of the enzyme and reduced production of superoxide anion in cHL.